Pemenuhan Kebutuhan Informasi Pemustaka di Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat - Fadhilah, Rahmi; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2014)
This article discusses Fulfillment pemustaka Information Library and Archives in West Sumatra province. Preparation of this article aims to describe: (1) the type of information needs of the visitors, and (2) the relevance of library materials to the needs of the visitors information. Relevance in the context of this study is defined as suitability, linkage or alignment between the library materials available to the needs of the visitors who use it. Based on analyzing the data summarized as follows: (1) the information needs of the visitors have not been fulfilled to the fullest because library materials are not required to follow the development of information and the latest updates or not. (2). based on the type of the visitors to the information needs of library materials available are less relevant to the information needs of the visitors. Keywords: fulfillment; need; information; library